ANALISIS PENGARUH TINGKAT HUTANG, ARUS KAS OPERASI DAN VOLATILITAS PENJUALAN TERHADAP PERSISTENSI LABA - Yunita Gunawan; Latersia Br Gurusinga (KRISNA: Kumpulan Riset Akuntansi, 2022)
Profit persistence can simply be interpreted as the possibility that a company's profit level will repeat itself in the future. This study aims to determine whether the level of debt, operating cash flow and sales volatility on earnings persistence in property and real estate companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The method of collecting data is by studying documentation obtained from secondary data in the form of financial reports downloaded from the IDX website. The population of property and real estate companies consists of 64 companies, the technique of determining the sample is using purposive sampling obtained a sample that meets the criteria for this study as many as 29 companies. The data analysis technique used is multiple linear regression analysis using SPSS version 25. The results of the test data show that the level of debt has a significant negative effect on earnings persistence, and operating cash flow and sales volatility have a positive effect on earnings persistence. level of debt, operating cash flow and sales volatility have a significant effect on earnings persistence. Suggestions for further researchers are to add other independent variables such as market characteristics, operating cycle and book tax difference or may also add a moderating variable Good Corporate Governance.